Analysis of Transformational Leadership and Work Environment on Employee Performance with Work Motivation as a Mediating Variable at the National Narcotics Agency of North Sumatra Province - Roy Fadly Hasibuan; Kiki Farida Ferine; Sri Rahayu (Journal of Management, Economic, and Accounting, 2026)
Employee performance is a strategic factor in supporting the success of government agencies, particularly the North Sumatra Provincial National Narcotics Agency (BNN), which faces complex and high-risk challenges. This study aims to analyze the influence of transformational leadership and work environment on employee performance with work motivation as a mediating variable. This study uses a quantitative approach with a census method of all 84 employees of the North Sumatra Provincial BNN. Data were collected through questionnaires and analyzed using the Partial Least Square (PLS) method with the help of SmartPLS. The results show that transformational leadership and work environment have a positive and significant effect on employee performance and work motivation. Work motivation was also found to have a positive and significant effect on employee performance. In addition, work motivation acted as a significant mediating variable in the relationship between transformational leadership and work environment on employee performance. These findings indicate that improving the performance of North Sumatra Provincial BNN employees can be achieved through the implementation of effective transformational leadership and the creation of a conducive work environment by strengthening employee work motivation. This study is expected to serve as a basis for policy recommendations in efforts to improve performance and the quality of public services within the North Sumatra Provincial Narcotics Agency.